Reestructuración administrativa y comercial para la empresa Bioplastic de Colombia S.A.S. (2020)
The project aims to analyze the commercial and administrative areas of Bioplastic Colombia SAS, in order to find the opportunities for improvement immersed in these. Proposing a commercial and administrative restructuring. The development of the project is based on the information provided by the organization in the time frame of 2020, the project is delimited by the city of Bogotá D.C. As an initial factor in the analysis, the diagnosis of the organization is established by identifying the internal and external factors in which it develops, using PESTAL analysis tools (national and district level) , DOFA, the self-diagnostic format of the Chamber of Commerce of Bogotá and the diagnosis of the sector and subsector. Subsequently, the market study was developed in which the clients were identified and the potential competition within the market niche where the company is immersed, through tools such as the 5 forces of Porter, segmentation and market research, thus determining the company’s current market position.